2006
DOI: 10.1111/j.1365-2826.2006.01444.x
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation in the Responsiveness of the Hypothalamic‐Pituitary‐Adrenal Axis of the Male Rat to Noise Stress

Abstract: Basal activity of the rat hypothalamic-pituitary-adrenal (HPA) axis is highly dynamic and displays both circadian and ultradian rhythmicity in corticosterone secretion. This study investigated the relationship between basal corticosterone pulsatility and the corticosterone response to noise during the early light phase when there are no endogenous corticosterone pulses and during the early dark phase when there are hourly pulses of corticosterone. An automated blood sampling system was used to collect blood in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 36 publications
8
55
0
Order By: Relevance
“…Release of glucocorticoids from the adrenal glands follows two superimposed temporal patterns: a daily (circadian) pattern and an hourly ultradian pattern (Lightman et al 2002Young et al 2004;Atkinson et al 2006;Lightman 2006;Droste et al 2008;Lightman and Conway-Campbell 2010;Walker et al 2012). The effects of GR activation are further influenced by the cell-specific chromatin landscape (Stalder et al 1980;John et al 2008John et al , 2011Biddie et al 2011;Siersbaek et al 2011;Mandrup and Hager 2012) and by the action of other transcription factors and chromatin modifiers Voss et al 2011;Miranda et al 2013b;Morris et al 2014) genome-wide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Release of glucocorticoids from the adrenal glands follows two superimposed temporal patterns: a daily (circadian) pattern and an hourly ultradian pattern (Lightman et al 2002Young et al 2004;Atkinson et al 2006;Lightman 2006;Droste et al 2008;Lightman and Conway-Campbell 2010;Walker et al 2012). The effects of GR activation are further influenced by the cell-specific chromatin landscape (Stalder et al 1980;John et al 2008John et al , 2011Biddie et al 2011;Siersbaek et al 2011;Mandrup and Hager 2012) and by the action of other transcription factors and chromatin modifiers Voss et al 2011;Miranda et al 2013b;Morris et al 2014) genome-wide.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids, the GR-activating hormones are released from the adrenal glands in a circadian, as well as highly pulsatile (ultradian) fashion-e.g., short (20 min) hourly pulses (Lightman et al 2002Young et al 2004;Atkinson et al 2006;Lightman 2006;Droste et al 2008;Lightman and Conway-Campbell 2010;Conway-Campbell et al 2011;Walker et al 2012). This pulsatile hormone release pattern is further influenced by the physiological and the psychological status of the animal.…”
mentioning
confidence: 99%
“…Rodent and primate genetic background further influences the duration and intensity of GC production, which are not necessarily linked to behavioural differences [23,103]. Time of day can further influence peak amplitude and duration of GC responses [104], and the sex and age of an organism affect response dynamics in humans and rodents [21,22,26,27,105,106].…”
Section: (B) Cues That Alter Glucocorticoid Productionmentioning
confidence: 99%
“…For instance, it has been argued that the diurnal changes in GC require splanchnic nerve integrity but are not mediated by differential responsiveness to ACTH (12). It has also been shown that the response to a mild stress failed to support increased HPA axis reactivity during the active period (13).…”
Section: G Lucocorticoid [Gc; Corticosterone (Cs) In Rodents Andmentioning
confidence: 99%